“Doutora, eu vim tentar a sorte”: o atalhar no Hospital Público João de Barros Barreto - TAVARES, Aderli Goes (Universidade Federal do Pará, 2017)
The study focused on users' access to public health services, in this case access to the University Hospital João de Barros Barreto (HUJBB), a hospital Unified Health System (SUS) located in the urban area in the neighborhood of Guama, in Belém, PA. The focus of the study were the social networks of relationships built by ‘guamaenses’ users to access medical consultations in medical clinic specialties, pulmonology, endocrinology at the hospital's specialty clinic. The informal approach was called "shortcuts" and is configured as an internal social organization that adds partial social networks (BARNES, 1987) external and internal. "Shortcuts" are part of a rhizome social structure (DELEUZE & GUATTARI, 2000), with entries for different spaces and a work process focused on designing hegemonic hospital-and philanthropic health. In hospitals, workers, particularly physicians, operate by "negotiated" (CARAPINHEIRO, 2005). The problem of inefficiency of SUS regulation to organize access and other SUS structural problems when the lower supply that demand prevents the exercise of universal access of citizens to health services and contribute to the discovery and building innovations for access , which Castoriadis (1982) interprets as "instituting" in an institution or what Carapinheiro (2005) points out as "therapeutic pathways." In case, the informal access in HUJBB is called "docking", the "door of hope" and was interpreted as a subsystem of the SUS, living with a syncretic public administration, with marks of public administration with rationalists impersonal principles and culture relational Brazilian. Between the rational and impersonal, SUS and marginality in the system, users and workers found the "gaps" in the formal system. They administer them through rational knowledge and relational and personalized, the very last of the formation of the Brazilian people, and use them to extend the standards and rules, they did not break the rules and do not make the "shortcut" the legal, and rather build a bridge within the SUS itself that makes it worth the recommended universal to access constitutionally Brazilians, reducing the waiting time and possibly allowing rehabilitate the health of users, preventing death.